OPTIMASI PROSES PRODUKSI EPOKSIDA RAMI (Linum Usitatissimum) TERHADAP KARAKTERISASI BILANGAN OKSIRAN - Flora Elvistia Firdaus (Program Studi Kimia Universitas Negeri Jakarta, 2011)
Conversion of edible oil; linseed oil (Linum Usitatissimum) to epoxide can be existed by using peracetic acid which can be applied by in situ method. The aim of the research was to identify the effect of temperature and catalyst to the oxirane number of linseed epoxide. The ratio of acetic acid to peroxide were 1/3,66; 1/3,74; 1/3,89; and 1/3,97 (mol/mol); with designated temperature of 600C and 700C, and amount of catalyst were 1,3; 1,5; 1,6; 1,7; and 2,0% (v/v). The highest oxirane number were achieved by the value of 5,8 % mgr KOH/gr with optimized ratio of reactants was1/3,74 and the amount of catalyst was 1,3% (v/v) at temperature of 600 C. The rising of temperature into 700C seems to be much effected in lowering the oxirane number. Keywords:linseed oil, epoxide, oxirane number, temperature, optimized